Environmental Health Study: Analysis of Linking Water Clean Access and Sanitation Levels with Public Health - Sari, Mita Permata; Andandaningrum, Della; Putri, Vera Chania; Sari, Dwi Meyta (WISE Pendidikan Indonesia, 2024)
Access to clean water and adequate sanitation is essential for public health and environmental sustainability. This study analyzes the relationship between water access, sanitation levels, and public health in Tanjung Karang Pusat, Tanjung Karang Timur, and Tanjung Karang Barat. Using a cross-sectional approach, data were collected through field observations, interviews, and questionnaires from 70 households. The findings indicate that 59% of households have safe drinking water access, while 7% still rely on unprotected sources and 4% have limited access to piped networks. In terms of sanitation, 34% of households have safe sanitation, while 56% have basic but self-sufficient access without regular desludging. However, 4% use shared toilets, 4% have direct waste disposal into the environment, and 1% still practice open defecation (BABS), posing serious health and environmental risks. The study highlights the disparities between urban and rural areas, where inadequate sanitation and limited water access increase the risk of waterborne diseases, economic losses, and environmental degradation. Addressing these challenges requires infrastructure improvements, public awareness campaigns, and policy interventions to ensure universal access to clean water and proper sanitation. Investment in sanitation and hygiene infrastructure is crucial to reducing disease burden, enhancing productivity, and supporting Sustainable Development Goal (SDG 6) on clean water and sanitation.